2022
DOI: 10.3389/frhs.2021.817750
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Silos: A Comparative Analysis of Implementation Science and Improvement Science

Abstract: BackgroundImplementation science and improvement science have similar goals of improving health care services for better patient and population outcomes, yet historically there has been limited exchange between the two fields. Implementation science was born out of the recognition that research findings and effective practices should be more systematically disseminated and applied in various settings to achieve improved health and welfare of populations. Improvement science has grown out of the wider quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…The KT-cnm (31) brings the ecologic basis of PROLIFERATE (defined in Table 1 and illustrated in Figure 3). Having the KT-cnm as a foundational component of PROLIFERATE is of interest to the field of IS because it means operationalizing a novel way of considering the evolving and emergent properties of the health systems and developing, identifying, implementing, and evaluating solutions that attempt to respond to the challenges presented in the introduction (22,31,37).…”
Section: Proliferate Ecological Logic: the Basis Of The Evaluationmentioning
confidence: 99%
“…The KT-cnm (31) brings the ecologic basis of PROLIFERATE (defined in Table 1 and illustrated in Figure 3). Having the KT-cnm as a foundational component of PROLIFERATE is of interest to the field of IS because it means operationalizing a novel way of considering the evolving and emergent properties of the health systems and developing, identifying, implementing, and evaluating solutions that attempt to respond to the challenges presented in the introduction (22,31,37).…”
Section: Proliferate Ecological Logic: the Basis Of The Evaluationmentioning
confidence: 99%
“…What happens in a dental practice, or any clinical service delivery system organization, is not simply a function of an individual's behavior. Those familiar with quality improvement and systems engineering will recognize that the performance of the system is a function of the design of the system itself 7,8 . Exhorting people to change their behavior in the context of a system that is not designed to support and promote the behavior is likely to be a fruitless and futile exercise 8 .…”
Section: Narrative Summary Of Panel Proceedingsmentioning
confidence: 99%
“…If you are familiar with the quality improvement approach, you will find the general process steps of implementation research to be familiar 7 . There are interesting similarities and differences between quality improvement research and implementation science, but in general if you are comfortable with quality improvement, you will find it easy to work with implementation scientists or dip your toe into doing some of it yourself.…”
Section: Narrative Summary Of Panel Proceedingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Deming (1986) Cycle principles are at the foundation of improvement science as it is referred to in education research. Although Shewhart's PDSA Model was largely ignored by educators during his lifetime, the learning and improvement tools are at the center of what has been adopted as IS-GR in education (Moen & Norman, 2010;Nilsen et al, 2022) and have also found traction in Japanese business and American manufacturing (Add Source).…”
Section: The Evolution Of Improvement Sciencementioning
confidence: 99%